Strategy and tactics of writing internal auditors' findings: Between discretion and harsh reality - Drvendžija Jelena (Bankarstvo, 2025)
In an effort to put into practice a modern approach whereby internal audit becomes a 'trusted advisor', the article discusses the obstacles that internal auditors face. A conceptual strategic model is then offered in which internal auditors can write their findings by defining observed problems as instabilities that need to be stabilized and as such consists of: a situation (instability), realistically possible consequences of the situation (risk), and a community-oriented perspective. Proposed model offers four tactical approaches to defining an audit finding: an approach focused on the detriment that instability brings to the community (that is, the benefits brought by solving the problem), an approach based on destabilizing the status quo, an approach based on an omission in practice or regulation, and an approach based on error. Through well-chosen and balanced formulation, the essence of the observed problem, internal auditors help the community to take further steps in its development.